Bariatric surgery in obese patients reduced resting connectivity of brain regions involved with self‐referential processing. Issue 12 (31st July 2018) - Li, Guanya; Ji, Gang; Hu, Yang; Xu, Mingzhu; Jin, Qingchao; Liu, Li; von Deneen, Karen M.; Zhao, Jizheng; Chen, Antao; Cui, Guangbin; Wang, Huaning; Zhao, Qingchuan; et al.
Abstract: Obese individuals exhibit brain alterations of resting‐state functional connectivity (RSFC) integrity of resting‐state networks (RSNs) related to food intake. Bariatric surgery is currently the most effective treatment for combating morbid obesity. How bariatric surgery influences neurocircuitry is mostly unknown. Functional connectivity density (FCD) mapping was employed to calculate local (lFCD)/global (gFCD) voxelwise connectivity metrics in 22 obese participants who underwent functional magnetic resonance imaging before and 1 month after sleeve gastrectomy (SG), and in 19 obese controls (Ctr) without surgery but tested twice (baseline and 1‐month later). Two factor (group, time) repeated measures ANOVA was used to assess main and interaction effects in lFCD/gFCD; regions of interest were identified for subsequent seed to voxel connectivity analyses to assess resting‐state functional connectivity and to examine association with weight loss. Bariatric surgery significantly decreased lFCD in VMPFC, posterior cingulate cortex (PCC)/precuneus, and dorsal anterior cingulate cortex (dACC)/dorsomedial prefrontal cortex (DMPFC) and decreased gFCD in VMPFC, right dorsolateral prefrontal cortex (DLPFC) and right insula ( p FWE < .05). lFCD decreased in VMPFC and PCC/precuneus correlated with reduction in BMI after surgery. Seed to voxel connectivity analyses showed the VMPFC had stronger connectivity with left DLPFC and weaker connectivity with hippocampus/parahippocampus, and PCC/precuneus had stronger connectivity with right caudate and left DLPFC after surgery. Bariatric surgery significantly decreased FCD in regions involved in self‐referential processing (VMPFC, DMPFC, dACC, and precuneus), and interoception (insula), and changes in VMPFC/precuneus were associated with reduction in BMI suggesting a role in improving control of eating behaviors following surgery.